(3fRgI GdCOHGA hSdhI GdZQHGAs
(3ChdgG (B:s
(3hHYO, abO SCdfj HYV GdeNGOe Cf CLeY dg eLehYkG ef GdfhGOQ GdeVMcI aCLHJg Edi Pdc s
(3BNQgG (B:s
(3hChOYJ ef cd fGOQI eVMcI YLjHI hfSCd Gddg GdeZaQI ced cJGH fRgI GdCOHGA hSdhI s
(3HgG fXGe GdJYbjHIs
(3aj LRAjf LeY ajg ef fhGOQ GdeZadjf hfhGOQ GdaVdGA hGdaVdjGJ hGdeYdejf hGdfMGI hGddZhjjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3fOhI GdYdeGA (B- (3dcfgh (B(357) s
Keywords: (3GdCOHs